Measurement of phenolic environmental estrogens in women with uterine leiomyoma. - Yang Shen; Qian Xu; Mulan Ren; Xu Feng; Yunlang Cai; Yongxing Gao (PLoS ONE, 2013)
To investigate the effect of phenolic environmental estrogens on uterine leiomyoma from the perspective of clinical epidemiology.Urine and blood samples were collected from Han women with uterine leiomyoma and women without uterine leiomyoma, living in Nanjing, China, between September 2011 and February 2013. A total of 156 urine samples and 214 blood samples were collected from the uterine leiomyoma group and 106 urine samples and 126 blood plasma samples from the control group. Bisphenol A (BPA), nonylphenol (NP) and octylphenol (OP) concentrations were determined by solid-phase extraction (SPE) coupled with liquid chromatography-tandem mass spectrometry (HPLC-MS/MS).Phenolic environmental estrogens in the uterine leiomyoma and control groups were compared based on: gravida>3 and gravida ≤ 3. In participants with gravida>3, urine OP concentration was significantly (P<0.05) higher in the uterine leiomyoma group than in the control group. In participants with gravida ≤ 3, urine NP concentration was significantly (P<0.05) higher in the uterine leiomyoma group compared to controls. Despite obstetric history, urine BPA mean exposure concentration was significantly (P<0.05) different between uterine leiomyoma group and control group. The urine BPA concentration was not significantly (P>0.05) different between gravida>3 and gravida ≤ 3 patients. There was no significant (P>0.05) difference in plasma concentrations of BPA, OP and NP between the leiomyoma group and control group. Mean exposure concentration and range of distribution of BPA, OP and NP plasma concentration differed between the uterine leiomyoma and control group.Exposure level of phenolic environmental estrogens in human was related with leiomyoma tumorigenesis.